MicroRNA-370 inhibits the proliferation, invasion and EMT of gastric cancer cells by directly targeting PAQR4 - Ye Feng; Tao Sun; Yabo Yu; Yongjian Gao; Xuefeng Wang; Zhi Chen (Elsevier, 2018)
It has been reported that PAQR4 (Progestin and AdipoQ Receptor 4) expression is closely associated with progression of many cancers and microRNA (miRNA) processing. However, the effects and its precise mechanisms of PAQR4 in gastric cancer (GC) have not been well clarified. Our study aimed to explore the interaction between PAQR4 and miR-370 in GC. In our study, we found that the miR-370 level was significantly down-regulated in GC tissues and cell lines, and the expression of PAQR4 was dramatically increased. Interestingly, the low miR-370 level was closely associated with up-regulated PAQR4 expression in GC tissues. Moreover, introduction of miR-370 dramatically suppressed proliferation, invasion and EMT of GC cells. Whereas, miR-370 knockdown increased the proliferation, invasion and EMT in GC cells. We demonstrated that miR-370 could directly target PAQR4 by using both bioinformatics analysis and luciferase reporter assay. In addition, PAQR4 silencing had the similar effects with miR-370 overexpression on GC cells. Overexpression of PAQR4 in GC cells partially reversed the inhibitory effects of miR-370 mimic. miR-370 inhibited cell proliferation, invasion and EMT of GC cells by directly down-regulating PAQR4 expression, and miR-370 targeting PAQR4 was responsible for inhibition of the proliferation, invasion and EMT of GC cells. Keywords: Gastric cancer, MicroRNA-370, PAQR4, Proliferation, Invasion